THE ROLE OF MUSEUMS IN HISTORICAL PUBLICATIONS - Erika Amanda Salsabila Putri (CV. Fahr Publishing, 2024)
This study aims to examine the role of museums in the publication of history, particularly in improving the quality of history education in Indonesia. History education museums function as both sources of information and learning media. As sources, they provide comprehensive historical knowledge, while as learning media, they facilitate the learning process through engaging methods, including the use of digital technology. Technologies such as social media, audiovisuals, and websites are utilized to expand the reach of historical publications. This research employs a qualitative method with a descriptive approach, gathering data through literature reviews from various sources, including books, journal articles, and online data. The data were analyzed inductively to derive holistic conclusions. The findings reveal that digital technologies, such as social media and audiovisual platforms, significantly enhance public accessibility and engagement in history learning. Museums adopting participatory approaches, such as interactive exhibitions and co-creation programs, create deeper and more personalized learning experiences for visitors. Thus, museums play a strategic role in publishing history and increasing public understanding of cultural heritage, with technology serving as the main tool to broaden the reach and appeal of history education.